Assessing temporal and spatial variability of algal bloom in Three Gorges Project reservoir----Application of an unstructured-grid three-dimensional coupled hydrodynamic-water quality model - Li, Jian (2016)
Patterns of temporal and spatial variability of algal bloom in Three Gorges Project (TGP) reservoir and the tributary Xiangxi River (XXR) were examined using SELFE, an unstructured-grid, three-dimensional, hydrodynamic-water quality model. Dynamics of phytoplankton biomass characterized by chlorophyll a, nutrients including organic and inorganic nitrogen and phosphorus, dissolved oxygen (DO) , suspended and bottom sediments were modeled using an expended and revised version of Water Analysis Simulation Program (WASP) which was fully coupled to SELFE model. The coupled model was driven by surface wind force, heat fluxes, oxygen exchanges at water-air interface, solar radiation and boundary conditions fluxes from Changjiang River (CJR) and XXR. The model was calibrated and verified by two time series of field observed data of algal blooms in TGP over the periods from September to October in 2007 and from June to July in 2008. The model results indicate that the stratified layers can form in the confluence zone between XXR and CJR because of water temperature three-dimensional distribution and also the water and nutrients interchange and backflow into the tributary XXR will influence the algal bloom process. The interactions between suspended and bottom sediment with nutrients and phytoplankton through adsorption and light attenuation were also considered. The developed model will provide a new tool to study the aquatic environmental problems in TGP.